2019
DOI: 10.3390/molecules25010004
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profiling and Stable Isotopic Data Analysis for Differentiation of Extra Virgin Olive Oils Based on Their Origin

Abstract: To differentiate extra virgin olive oils (EVOO) according to the origin of purchase, such as monocultivar Italian EVOO with protected denomination of origin (PDO) and commercially-blended EVOO purchased in supermarkets, a number of samples was subjected to the analysis of various lipid species by liquid chromatography/mass spectrometry (LC-ESI-MS/MS, LC-ESI-IT-MS) and proton nuclear magnetic resonance analysis ( 1 H-NMR). Many putative chemical markers were extracted as differentiators by uni-and multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…EVOO has been widely studied because of its effects in preventing several metabolic diseases and pathologies, such as atherosclerosis, cardiovascular diseases, serum lipoprotein levels, oxidative stress, obesity, type 2 diabetes, inflammation and cancer [1][2][3][4][5]. Overall, the health-promoting effects of EVOO are mainly related to its inherent chemical composition, such as the fatty acid profile [6] rather than other "minor" components (nearly 2% of the total weight). This quantitatively lower fraction includes more than 200 chemically different compounds belonging to aliphatic alcohols, terpenoids, sterols, pigments, volatile compounds and (poly)-phenolic compounds [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…EVOO has been widely studied because of its effects in preventing several metabolic diseases and pathologies, such as atherosclerosis, cardiovascular diseases, serum lipoprotein levels, oxidative stress, obesity, type 2 diabetes, inflammation and cancer [1][2][3][4][5]. Overall, the health-promoting effects of EVOO are mainly related to its inherent chemical composition, such as the fatty acid profile [6] rather than other "minor" components (nearly 2% of the total weight). This quantitatively lower fraction includes more than 200 chemically different compounds belonging to aliphatic alcohols, terpenoids, sterols, pigments, volatile compounds and (poly)-phenolic compounds [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although their study shows that the use of stable isotopes is an efficient tool for the verification of provenance, other analytical variables such as multi-element profiles, spectroscopic fingerprinting and chemical profiling are needed to improve classification accuracy [ 9 ]. Fatty acid profiling, when combined with various chemometric tools, has been successfully applied to discriminate the geographical origin of vegetable oils including olive oil [ 10 , 11 ], pumpkin oil [ 10 , 12 ] and Sativa oils [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oleanolic acid is a triterpenoid abundant in olive oil (26.71–50.13 μg) ( 75 ) with previous studies (>5 years prior to this review) that had demonstrated anti-proliferative capacity in both MDA-MB-231 TNBC and MCF7 luminal A BC cells with respective half maximal inhibitory concentrations (IC 50 ) of 7.0 and 7.5 μM ( 107 ). These anti-proliferative effects were attributed to induced cell cycle arrest and apoptosis in these cell lines.…”
Section: Olive Oil and Tnbc: Reviewmentioning
confidence: 76%
“…Searches for fish oil returned studies that focused on the ω-3 essential fatty acids docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). For olive oil, we included studies looked at several of the polyphenolic compounds that are abundant in olive oil and the 18:1 monounsaturated fatty acid oleic acid, which is the predominant free fatty acid in olive oil ( 75 ). The studies we reviewed performed cell culture experiments with TNBC cell lines and some of these ( 41 , 48 , 53 56 , 69 , 71 , 72 ) extended their experiments in vivo .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation